A Sensitive Resonance Rayleigh Scattering Method for Na+ Based on Graphene Oxide Nanoribbon Catalysis - Haidong Wang; Chongning Li; Yanghe Luo; Zhiliang Jiang (International Journal of Analytical Chemistry)
The gold nanoparticle reaction of HAuCl4-H2O2 was very slow under 60°C, and the as-prepared graphene oxide nanoribbons (GONRs) exhibited strong catalysis of the reaction to form gold nanoparticles (AuNP) that appeared a resonance Rayleigh scattering (RRS) peak at 550 nm. Upon addition of potassium pyroantimonate (PA) ligand, it was adsorbed on the GONRs surface to inhibit the catalysis to cause the RRS peak decreasing. When the analyte of Na+ was added, the coordination reaction between PA and Na+ took place to form the stable complexes of [Na2(PA)] to release free GONRs catalyst that resulted in the RRS peak increasing linearly. Accordingly, a new and sensitive RRS method for Na+ was established, with a linear range of 0.69-25.8 nmol/L and a detection limit of 0.35 nmol/L Na+.